Pacing the Curriculum in the Context of School Realities - Larry Giacomino; Michael Gose (Networks: An Online Journal for Teacher Research, 2002)
Our topic became: pacing the curriculum in the context of school realities. Our 'study' stemmed from our long conversations about teaching and our observations about the changes we had each made over the years to adjust to the ebb and flow of the school year. (We believe that this is "action research" because it has been all about "making changes and observing their effects"-- but it may be one of the longest running action-research studies in that it has taken us over thirty years to articulate our conclusions.) From those conversations we developed a prototype of factors, conditions, variables, that we personally found tend to influence pacing the curriculum in the day, week, month, term, year. We found that the changes we had both made with regard to pacing the curriculum were almost identical. For a "reality check" on our findings, we then surveyed twenty-four other secondary teachers, teachers with reputations for being strong teachers to see if there was agreement about the importance of the factors we had identified and to see what else they might add to this ongoing conversation. Based on our reflection about our own experiences, and our survey of twenty-four of our peers, we found general support for the idea that the factors we identified have strong external influences on the pacing and the rhythm of the curriculum. While we think there is value for teachers in considering the factors that we identified, we felt that the greater richness of our study came in the written comments by the teachers we surveyed. On the basis of their remarks we found evidence that effective teachers have adapted to these factors to mitigate against their becoming negative factors, and that at least certain teachers have a rich repository of knowledge about the art of pacing the curriculum.